2022
DOI: 10.3390/molecules27030731
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Management of Bladder Cancer—The Role of Photodynamic Therapy

Abstract: Photodynamic therapy (PDT) is a non-invasive and modern form of therapy. It is used in the treatment of non-oncological diseases and more and more often in the treatment of various types of neoplasms in various locations including bladder cancer. The PDT method consists of local or systemic application of a photosensitizer, i.e., a photosensitive compound that accumulates in pathological tissue. Light of appropriate wavelength is absorbed by the photosensitizer molecules, which in turn transfers energy to oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 103 publications
0
22
0
Order By: Relevance
“…Among the most important advantages of PDT is low systemic toxicity because the cytotoxic effect of the PS in the absence of light irradiation is several orders of magnitude lower than in the irradiated cancer tissue. But a current limitation is the mode of light delivery, which is currently restricts treatment to superficial tumors or tumors accessible with an endoscope: non-melanoma skin cancer [ 206 ], retina and ocular malignancies [ 207 ], cancer of the digestive tract [ 208 ], urinary system malignancies [ 209 , 210 ], tracheobronchial malignancies [ 211 ], and cervical cancer [ 212 ]. Also, PDT was shown to be effective in improving patient prognosis when used after surgical resection of glioblastoma [ 213 , 214 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important advantages of PDT is low systemic toxicity because the cytotoxic effect of the PS in the absence of light irradiation is several orders of magnitude lower than in the irradiated cancer tissue. But a current limitation is the mode of light delivery, which is currently restricts treatment to superficial tumors or tumors accessible with an endoscope: non-melanoma skin cancer [ 206 ], retina and ocular malignancies [ 207 ], cancer of the digestive tract [ 208 ], urinary system malignancies [ 209 , 210 ], tracheobronchial malignancies [ 211 ], and cervical cancer [ 212 ]. Also, PDT was shown to be effective in improving patient prognosis when used after surgical resection of glioblastoma [ 213 , 214 ].…”
Section: Introductionmentioning
confidence: 99%
“…PDT has been used to treat a variety of cancers, including lung, head and neck, brain, pancreas, peritoneal cavity, breast, prostate, skin, and liver cancer ( Kubrak et al, 2022 ).…”
Section: The Applications and The Photosensitizers For Clinical Tumor...mentioning
confidence: 99%
“…Similar to PDD, photodynamic therapy (PDT) induces cell death through the production of reactive oxygen species [203,204]. Filonenko et al reported that PDT with 5-ALA caused 22% recurrence for patients with NMIBC in the first year after treatment [205].…”
Section: Photodynamic Therapymentioning
confidence: 99%